Impact of Mental Health Awareness Programs on Nurse's Well-being and Patient Care - Jane Anderson; Michael Harris; Laura Robinson (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
This study investigates the impact of mental health awareness programs on nurses’ well-being and the quality of patient care. By evaluating the effectiveness of training programs aimed at improving mental health literacy among nurses, the research explores how better mental health awareness enhances nurse resilience, reduces burnout, and improves patient outcomes. The findings suggest that promoting mental health education for nurses is crucial for creating a healthier work environment and providing better patient care.